Effectiveness of Impulse Control Training in Self-Efficacy of High School Students - Shahrbanoo Ghahari (Journal of Global Pharma Technology, 2017)
Introduction and Objective impulsive behaviors are dysfunctional behaviors that harm others; hence, it is essential to teach some methods to control impulses. In this regard, this study was conducted to examine effectiveness of impulse control training on self-efficacy among high school students. Materials and Methods this is an experimental with pretest-posttest plan. Statistical population of study consisted of all students educating at first grade of high school in Roodsar, Iran; in this regard, 60 students that were not able to control impulse were selected as sample size form several schools through purposeful method then were assigned into two 30-members groups (control and experimental). Then, Sherer Self-efficacy Questionnaire was distributed among members in both groups within pretest then experimental groups received the protocol of impulse control training and control group remained in waiting list; ultimately, self-efficacy questionnaire was again distributed among members in both groups to examine effect of impulse control training protocol as posttest. The obtained data were analyzed using ANCOVA through SPSS22 Software. Findings the obtained results showed that impulses control training could affect self-efficacy of students (P<0.005). Conclusion it is concluded in accordance with obtained findings that impulse control training can increases self-efficacy among students.Keywords: Impulse Control, Self-Efficacy, High School Students.